The Bahamas : 2005 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Bahamas. (IMF Staff Country Reports; Country Report ;, 2005)
The Bahamas's 2005 Article IV Consultation reports that the economic slowdown has contributed to deterioration in the fiscal accounts. The Bahamas is a small, open, and relatively wealthy economy, which is highly dependent on tourism from the United States and offshore financial activities. Offshore financial activities have developed rapidly since the early 1990s and account for roughly 15 percent of GDP. This has reduced the economy's dependence on the tourism sector, which is focused on the higher end of the U.S. market but still accounts for one-fourth of GDP.